Methodology System and Application of Technology Foresight on China's Engineering Science and Technology Toward 2040 - Xiaoji Zhou; Yongwei Zhang; Shoulei Ma; Li Sun; Tingfeng Huang; Shengkai Sun; Xinyi Chen; Wenjiang Zheng; Yufei Liu (中国工程科学)
The Research on the Technology Foresight of China's Engineering Science and Technologies Toward 2040 is jointly organized by the Chinese Academy of Engineering and the National Natural Science Foundation of China. As an important component of the research on China's engineering science and technology development strategy to 2040, it aims to predict the general trend of scientific and technological development and clarifying the key engineering science and technologies and development directions that may yield major breakthroughs. To improve the forward-looking and scientific nature of the technology foresight, this study evaluates the effectiveness of the technology foresight from two aspects: application of the technology foresight methodology and impact of the foresight results. Following the idea of emphasizing demand traction and vision drive as well as combining expert judgment and multi-source big data intelligent analysis, this study designed a methodology system, developed the intelligent Support System (iSS) for strategic studies on engineering science and technology, and constructed a standardized process centered on experts, supported by data, and facilitated by interaction, thus to push forward the implementation of the technology foresight. The study has formed a list of alternative technologies containing over 900 items in 11 fields, conducted two rounds of Delphi expert surveys, and proposed 110 domain core technologies, 25 key common technologies, and 21 disruptive technologies, thereby providing an important support for the research on China's engineering science and technology development strategy to 2040.